2022
DOI: 10.1038/s41467-022-33510-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequence analysis of blood lipid levels in >66,000 individuals

Abstract: Blood lipids are heritable modifiable causal factors for coronary artery disease. Despite well-described monogenic and polygenic bases of dyslipidemia, limitations remain in discovery of lipid-associated alleles using whole genome sequencing (WGS), partly due to limited sample sizes, ancestral diversity, and interpretation of clinical significance. Among 66,329 ancestrally diverse (56% non-European) participants, we associate 428M variants from deep-coverage WGS with lipid levels; ~400M variants were not asses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 99 publications
(132 reference statements)
1
14
0
1
Order By: Relevance
“…However, precision medicine by deep genetic analysis helps improving the diagnosis and the management of patients. An application of genome sequencing in relation to lipid traits was recently published highlighting that this approach can identify new causative loci, new variants in gene-regions usually not analyzed and can be even used to evaluate PRS [ 86 ].…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…However, precision medicine by deep genetic analysis helps improving the diagnosis and the management of patients. An application of genome sequencing in relation to lipid traits was recently published highlighting that this approach can identify new causative loci, new variants in gene-regions usually not analyzed and can be even used to evaluate PRS [ 86 ].…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Blood lipids are complex traits that are influenced by genetics, the environment, and the gene-environment interaction. 44,45 Hence, populations with different genetics might display different phenotypes, 44 especially considering the important differences in diet between China and western countries. 46 However, previous studies also reported contrary results regarding the relationship between BMI and DPN.…”
Section: Author Contributionsmentioning
confidence: 99%
“…Despite the description of several associations with rare variants, it is still unclear how much they contribute to the heritability of human complex traits. This proportion is especially hard to estimate for rare variants as they correspond to observations only in a few individuals resulting in high standard errors 10 . As common variants are present in more individuals, it is expected that they will contribute more to the phenotypic variance than rare variants.…”
Section: Advantages Of Wgsmentioning
confidence: 99%
“…For example, an intronic variant of TNRC18 strongly associated with IBD but almost absent from other European populations 20 . WGS in diverse populations represents one of the most active areas of research, as getting an overview of the genetic architecture in diverse populations will enable better comprehension of complex diseases as well as the differences in effect direction and sizes of the associated variants that are observed across populations 10 .…”
Section: Advantages Of Wgsmentioning
confidence: 99%
See 1 more Smart Citation